2020
DOI: 10.1920/bn.ifs.2020.bn0300
|View full text |Cite
|
Sign up to set email alerts
|

Will universities need a bailout to survive the COVID-19 crisis?

Abstract: The ongoing COVID-19 crisis poses a significant financial risk to the UK higher education sector. Universities are facing big losses across a range of income sources and investments. These losses could cause serious financial problems, including -in the extreme -insolvency. Most institutions will be left with reduced net assets, which could increase financing costs and will leave them less well placed to cope with future adverse shocks.This briefing note examines the resilience of university finances to the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The stratification of UK’s higher education sector is also represented in the distribution of resources and student profiles. Those research-intensive universities, including the Russell Group and former 1994 Group, receive the largest share (62.3%) of government funding for research with other institutions receiving significantly less (De Jager, 2011; Drayton and Waltman, 2020). Whereas, Post-1992 institutions attract much more diverse student populations and receive more than 70% of the (much smaller) widening participation funds provided by the government (O’Connell, 2015).…”
Section: Uk Higher Education Sectormentioning
confidence: 99%
“…The stratification of UK’s higher education sector is also represented in the distribution of resources and student profiles. Those research-intensive universities, including the Russell Group and former 1994 Group, receive the largest share (62.3%) of government funding for research with other institutions receiving significantly less (De Jager, 2011; Drayton and Waltman, 2020). Whereas, Post-1992 institutions attract much more diverse student populations and receive more than 70% of the (much smaller) widening participation funds provided by the government (O’Connell, 2015).…”
Section: Uk Higher Education Sectormentioning
confidence: 99%
“…For example, data shows that U.K. universities generate a gross value-added contribution of £21.5 billion to GDP, which is much higher than many industries (Universities UK 2017). Meanwhile, it is estimated that the total long-run financial losses resulting from the pandemic for higher education in the U.K. could reach £11 billion, which is more than a quarter of the income in one year (Drayton and Waltmann 2020). The situation is worse in countries where universities are not shielded by governments' stimulus packages.…”
Section: Why the Higher Education Sector Matters?mentioning
confidence: 99%
“…Driven by the common understanding that education can lead to economic benefits, citizens often enol in education or training to boost their chances of finding employment or to enhance their income generating opportunities. The Institute of Fiscal Studies has shown that 80% of students gain financially from attending university -so when the need for economic growth is the greatest (during recessions and economic downturns), we may see an even greater demand for education in order to improve livelihood prospects (Drayton & Waltman, 2020). Moreover, as some occupations and industries lose relevance and others emerge as essential, there will be a need for extensive reskilling to meet labour market needs.…”
Section: Vocational Training and Informal Learningmentioning
confidence: 99%